Implementation of Beef Self-Support Program at the Department of Food Security and Livestock of North Sumatra Province - A Agung Pawiro; Rudi Kristian P. Manurung (Budapest International Research and Critics University, 2022)
The purpose of this study was to describe the implementation of the beef self-sufficiency program at the Department of Food Security and Livestock in North Sumatra Province. This study uses the Van Meter and Van Horn theory covering standards and policy objectives, resources, communication, characteristics implementing agents, implementor dispositions, and social, economic and political conditions. The method used is a descriptive method with a qualitative approach. Data collection techniques in this study using interview techniques, observation and documentation. The results show that the implementation of the Beef Self-Sufficiency Program in North Sumatra has been effective, namely an increase in the cattle population for several years starting from 2013 to 20017, this is in accordance with the production achievement target of the Food and Animal Husbandry Service of North Sumatra Province which wants to increase production achievements beef from year to year. However, the implementation of the Beef Self-Sufficiency program in North Sumatra province is still ineffective because of the lack of cooperation between related agencies, then as the target of this program, this program assistance has not been distributed to various farming communities. The inaccessibility of the location of breeders and the lack of field technical officers are still major factors inhibiting the implementation of this program.